3D finite element modelling and experimental researches on turning steel AISI1013 by nano-crystalline Al2O3 ceramics cutter. (1st January 2013) - Hu, H-J.; W-J. Huang,; Wu, G.S.
Tool wear is an important problem in turning of alloys by tool especially for nano-crystalline Al2 O3 ceramics cutter. Coupled thermo mechanical finite element modelling of 3D metal turning of alloy steel AISI1013 by nano-crystalline ceramics tool have been investigated by utilising DEFORM-3D simulations. Conditions of initial and boundary and turning process parameters have been applied in simulation process. The highest temperature rises of tool tip are below the temperature of dynamic recrystallisation, so the nano-Al2 O3 ceramics tool has better thermal stability. The reasons of force dropping and total wear increasing are the temperature rise in the tool tip, bigger turning forces could improve the wear rates. Through these researches more turning parameters can be estimated and it could be helpful to predict the variation of cutting force, cutting tool wears and temperature evolutions. The obtained results provide the fundamental and practical guidelines for the metal turning by nano-crystalline ceramics tool.